Axisymmetric mixed convective MHD flow over a slender cylinder in the presence of chemically reaction - Prasad, Kerehalli Vinayaka; Vaidya, Hanumesh; Vajravelu, Kuppalapalle; Datti, P.S.; Umesh, V. (Zielona Góra: Uniwersytet Zielonogórski)
The present analysis is focused on the study of the magnetic effect on coupled heat and mass transfer by mixed convection boundary layer flow over a slender cylinder in the presence of a chemical reaction. The buoyancy effect due to thermal diffusion and species diffusion is investigated. Employing suitable similarity transformations, the governing equations are transformed into a system of coupled non-linear ordinary differential equations and are solved numerically via the implicit, iterative, second order finite difference method.
Keywords: magnetic field; chemical reaction; heat transfer; mass transfer; convective flow; slender cylinder; Grashof number; Keller-Box method